2011
DOI: 10.1161/circulationaha.110.004762
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Clinical and Angiographic Outcomes of a Randomized Comparison of Sirolimus-Eluting and Paclitaxel-Eluting Stents

Abstract: Background-Long-term comparative data of first-generation drug-eluting stents are scarce. We investigated clinical and angiographic outcomes of sirolimus-eluting (SES) and paclitaxel-eluting stents (PES) at 5 years as part of the Pϭ0.29). Between 1 and 5 years, the annual rate of target lesion revascularization was 2.0% (95% confidence interval, 1.4% to 2.6%) for SES and 1.4% (95% confidence interval, 0.9% to 2.0%) for PES. Among patients undergoing paired angiography at 8 months and 5 years, delayed lumen lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(51 citation statements)
references
References 31 publications
6
41
1
3
Order By: Relevance
“…Although rates of target lesion revascularisation during the first year in the present study were very much comparable to those observed following treatment of native coronary artery lesions, recurrent ischaemia related to the stented segment became increasingly apparent at a later time, suggesting a considerable lack of long-term efficacy. Specifically, annual rates of TLR between the first and fourth year of follow-up were 50 to 70% higher compared with annual rates previously reported in the context of native coronary artery disease 16 . Therefore, SVG lesions continue to represent an important lesion subset with inadequate efficacy following the use of newergeneration DES.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although rates of target lesion revascularisation during the first year in the present study were very much comparable to those observed following treatment of native coronary artery lesions, recurrent ischaemia related to the stented segment became increasingly apparent at a later time, suggesting a considerable lack of long-term efficacy. Specifically, annual rates of TLR between the first and fourth year of follow-up were 50 to 70% higher compared with annual rates previously reported in the context of native coronary artery disease 16 . Therefore, SVG lesions continue to represent an important lesion subset with inadequate efficacy following the use of newergeneration DES.…”
Section: Discussioncontrasting
confidence: 55%
“…Similarly, in the Extended Duration of the Reduction of Restenosis In Saphenous vein grafts with Cypher stent (DELAYED RRISC) study 15 , rates of MACE amounted to 58% among SES-treated patients at a median follow-up of 32 months. These figures contrast with rates of MACE in the range of 20% among unselected patients enrolled in all-comers studies with the predominant treatment of native coronary artery lesions [16][17][18] .…”
Section: Discussionmentioning
confidence: 98%
“…However, a 5-year follow-up showed no differences in clinical and angiographic outcomes between the two DES [12]. In our study, there was no difference in target lesion revascularization between sirolimus-and paclitaxel-eluting stents (21.0% vs. 16.4% at 8 years, respectively, Log rank P ¼ 0.654), supporting a late catch-up phenomenon of sirolimus-eluting stents.…”
Section: Discussionsupporting
confidence: 45%
“…There were 3 trials [14][15][16] Table 2). Most trials addressed the method for sequence generation and allocation concealment.…”
Section: Characteristics Of Eligible Trials and Risk Of Biasmentioning
confidence: 99%